Measuring aggregate trade costs and its empirical effects on manufacturing export composition in China - Tongsheng Xu; Xiao Liang (China Finance and Economic Review, 2017)
Background: This paper measures the aggregate trade costs from 2000 to 2013, and dicusses the impact of China's aggregate trade costs on comparative advantages and export share of 17 two-digit ISIC manufacturing industries. Methods: This paper takes China's vertical specialization reality into account and establishes the panel data model which relates the aggregate trade costs with the export shares. Results: We find that China's aggregate trade costs are declining, but it is still 1/3 higher than that of developed countries of 10 years ago; bilateral trade costs between China and some countries even risen instead; aggregate trade costs are the determinants, not only of 'global' and 'local' comparative advantages, but also of export share of China's manufacturing products, and its effect is stronger in industries with higher trade cost intensity. Conclusions: We should consider the product composition on trade cost intensity and domestic value-added reseller (DVAR), and reduce trade costs in order to promote the export of products with higher domestic value-added rate, and to realize the substantial transformation of foreign trade growth mode.
Keywords: 330; Aggregate trade costs; Manufacturing export composition; Trade cost intensity; Domestic value added